Lateral approach in robotic total knee arthroplasty for valgus knees: A step-by-step technique - Andriollo Luca; Gregori Pietro; Koutserimpas Christos; Servien Elvire; Batailler Cécile; Kouyoumdjian Pascal; Lustig Sébastien (SICOT-J)
Total knee arthroplasty (TKA) in valgus knee deformities presents unique challenges, including alignment, soft tissue balance, and implant positioning. The lateral approach offers advantages over the traditional medial approach by improving direct access, patellar tracking, and soft tissue preservation. Robotic-assisted TKA enhances precision, ligament balancing, and patient-specific alignment strategies, such as functional knee positioning (FKP). This study describes a surgical technique integrating the lateral approach with robotic-assisted TKA using FKP principles. The technique is based on an image-based robotic system, ensuring accurate preoperative planning, intraoperative adjustments, and optimized prosthetic placement. Key intraoperative steps, including bone resection strategies, soft tissue balancing, and trial component evaluations, are detailed. The lateral robotic approach with FKP was found to be effective and reproducible, allowing for precise implant alignment and optimized soft tissue balance in valgus knees. This method minimizes the need for extensive lateral releases, preserves vascularity, and ensures postoperative stability. The combination of the lateral approach, robotic-assisted TKA, and FKP represents a promising strategy for valgus knee deformities. Further long-term studies are needed to validate the durability and functional benefits of this technique.